INFLUENCE OF THE NAUSEA AND VOMITING REFLEX IN PROSTHETIC TREATMENT OF PATIENTS WITH HOMEOPATHIC MEDICINES - A CASE REPORT - Tsvetelina Kanlieva; Kalina Georgieva; Metodi Abadjiev (Peytchinski Publishing, 2023)
Prosthetic treatment of a patient with manifested nausea reflex could be a dramatic experience. There is a risk of aspiration or ingestion of foreign objects, and the dentist may have great difficulties during the procedures. Purpose: The purpose is to report the efficiency of homeopathic medicines in the case of prosthetic treatment with removable dentures of a patient with a gag reflex and several medical conditions. There is a risk of aspiration of foreign bodies. This leads to compromises in the final treatment quality and difficulty wearing a denture because of gagging. Homeopathy is a safe and natural alternative that finds application in dentistry. Material/Methods: A case of a female patient is reported. Age of 63 with accompanying diseases. The patient has an exaggerated gag reflex during intraoral examination and needs prosthetic treatment with removable dentures. The gag reflex was assessed by the Classification of Gagging Problem Index (CGP), and examination of reflex reaction with a sterile swab and monofilaments were done before and after the reception of homeopathic medicines. Results: During the first and second visits, the results of the CGP index were recorded in the patient's clinical record. The results of the tests with the monofilaments and the sterile swab before and after taking homeopathic medicines were filled in tables and were compared. Conclusions: A satisfactory, harmless and long-lasting result in the reduction of the nausea reflex is achieved in the reported case by homeopathic medicines. All clinical stages of removable dentures' fabrication were possible, and the patient tolerated the new prostheses pretty well.